Measurement of photon-jet transverse momentum correlations in 5.02 TeV Pb + Pb and pp collisions with ATLAS - Alconada Verzini, María Josefina (2019)
Jets created in association with a photon can be used as a calibrated probe to study energy loss in the medium created in nuclear collisions. Measurements of the transverse momentum balance between isolated photons and inclusive jets are presented using integrated luminosities of 0.49 nb−1 of Pb + Pb collision data at √sNN = 5.02 TeV and 25 pb−1 of pp collision data at √s = 5.02 TeV recorded with the ATLAS detector at the LHC. Photons with transverse momentum 63.1 < pγ T < 200 GeV and ηγ < 2.37 are paired with all jets in the event that have pjet T > 31.6 GeV and pseudorapidity ηjet < 2.8. The transverse momentum balance given by the jet-to-photon pT ratio, xJγ , is measured for pairs with azimuthal opening angle φ > 7π/8. Distributions of the per-photon jet yield as a function of xJγ , (1/Nγ )(dN/dxJγ ), are corrected for detector effects via a two-dimensional unfolding procedure and reported at the particle level. In pp collisions, the distributions are well described by Monte Carlo event generators. In Pb + Pb collisions, the xJγ distribution is modified from that observed in pp collisions with increasing centrality, consistent with the picture of parton energy loss in the hot nuclear medium. The data are compared with a suite of energy-loss models and calculations.